2010
DOI: 10.1152/physiolgenomics.00004.2010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signatures and new candidates to target the pathogenesis of rheumatoid arthritis

Abstract: A, Neidel J, Lehrach H, Thiesen HJ, Ruiz P, Bläß S. Molecular signatures and new candidates to target the pathogenesis of rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
103
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 72 publications
2
103
0
Order By: Relevance
“…PMN) may adhere to cartilage, leading to destruction of cartilage. It has been reported that low expression levels of lubricin were associated with a strong synovial stromal activation (22), characterized by the infiltration of T cells and macrophages, and was associated with a higher destructive potential and a worse prognosis (63). Prg4 knock-out mice exhibited a degenerative phenotype, including synovial hyperplasia and abnormal cartilage surface (64).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PMN) may adhere to cartilage, leading to destruction of cartilage. It has been reported that low expression levels of lubricin were associated with a strong synovial stromal activation (22), characterized by the infiltration of T cells and macrophages, and was associated with a higher destructive potential and a worse prognosis (63). Prg4 knock-out mice exhibited a degenerative phenotype, including synovial hyperplasia and abnormal cartilage surface (64).…”
Section: Discussionmentioning
confidence: 99%
“…Loss-of-function mutations in the PRG4 gene causes the camptodactyly-arthropathy-coxa vara-pericarditis syndrome in humans, a syndrome of precocious joint failure associated with non-inflammatory synovial hyperplasia and subintimal fibrosis of the joint capsule (3). Lubricin is found heterogeneously expressed in the synovium of rheumatoid arthritis (RA) and osteoarthritis (OA), implying a role in the pathogenesis of these diseases (21,22). RA patients varied with respect to lubricin expression, where the patients with low levels of lubricin had more aggressive joint disease (22).…”
Section: Lubricin (Or Proteoglycan 4 (Prg4)mentioning
confidence: 99%
See 1 more Smart Citation
“…We used microarray dataset GSE1919 from GEO (www.ncbi.nlm.nih.gov/geo/) (Ungethuem et al, 2010). In this genome-wide dataset, the two disease conditions of RA and OA were investigated and the data were compared to those of normal donors (NDs).…”
Section: Data Collection and Pre-processingmentioning
confidence: 99%
“…Accordingly, to understand fundamental mechanisms of RA pathogenesis, it is essential to identify and analyze RA-perturbed networks in the RA synovium. Several studies have identified RA-associated genes (RAGs) and their associated cellular processes [4,5,6]. For example, Hurber et al [4] analyzed mRNA expression profiles in the synovial tissues of RA patients and normal controls.…”
Section: Introductionmentioning
confidence: 99%